54 Digestibility of forages in ruminally cannulated Jersey steers supplemented with liquid glycerol on a wheat straw forage diet. (29th July 2019) - Soto, Itzel A; Boyd, Jamie
Abstract: The purpose of this study was to determine the impact of supplementation of glycerol at a rate of 15% of DMI on forage digestibility on a diet of mature wheat hay. Forages tested included bermuda hay, wheat hay, alfalfa hay, and sorghum sudan hay. Samples were ground through a 2mm screen and placed in Ankom forage in-situ bags. Samples were run in triplicate to reduce error and increase statistical significance. Two ruminally cannulated steers were used in a 2x2 Latin square design for the study with ad libitum access to wheat hay and water. Animals were housed in a dry lot pen for the study. Diets offered were Control = wheat hay and Treatment= control + glycerol at 15% of daily DMI. The study consisted of 2 three-week periods. Each period had a 2-week standardization followed by a 1-week test period. During the test period, forage bags were placed in each steer for 0 h, 48 h, 72 h, 96 h, and 144 h for fermentation. At the end of the incubation period, bags were collected and cold shocked to stop microbial digestion. The samples were then dried at 55°C and stored for later analysis for NDF. A significant impact on NDFdig by treatment (P < 0.0001) was observed. NDFdig was 59.2% w/ glycerol versus control at 49.13% overall. In addition, there was a significant difference between steers (P = 0.0001) on glycerol treatment (51.95% versus 66.45% NDFdig between steer A and B), indicating difference in ruminal population efficiency between individual animals. No significant difference (P = 0.98) between steers on the control treatment was observed. Implications of this study are the inclusion of dietary glycerol in the diet of ruminants on a low-quality forage diet may increase energy level and improve ruminal digestibility and animal response may be dependent on the unique ruminal environment of individual animals.